Pengaruh Waktu Kontak Dan Laju Pengadukan Terhadap Adsorpsi Zat Warna Pada Air Gambut Menggunakan Adsorben Limbah Biosolid Land Application Industri Minyak Kelapa Sawit - Irpan Syafrianda; Elvi Yenie; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peat water is a type of surface water that contains natural organic materials, so that cause brownish-colored water, taste and smell, in addition to the color of peat water caused by organic acid. It viewed from quality, peat water has not include the standard of drink water quality standard. Peat water needs treated to be used as a source of clean water and drink water. The adsorption process can be one of the peat water treatment alternatives by utilizing one of agricultural industry waste in the form of biosolid Palm Oil Industry as natural adsorben. The purpose of this research is to know the effect of stirring speed and contact time on colour in peat water. In this study, variations of stirring speeds were used at 90, 120 and 150 rpm and contact time variation at 30, 60, 90 and 120 minutes. The best results at 150 rpm stirring speed and 90 minutes contact time were found to decrease the efficiency of colour degradation is 238,400 mg/g and efficiency decrease equal to 68,703%.Keywords: Peat water, Biosolid, Adsorption